Nuclear damage in peripheral lymphocytes of obese and overweight Italian children as evaluated by the γ-H2AX focus assay and micronucleus test - Scarpato, Roberto; Verola, Carmela; Fabiani, Barbara; Bianchi, Vanessa; Saggese, Giuseppe; Federico, Giovanni (The FASEB journal, 2011)
Childhood obesity, often characterized by a chronic low-grade inflammation, has been associated with an increased risk of developing some types of cancer later in life. Nuclear γ-H2AX foci represent the first detectable response of cells to DNA tumorigenesis lesions, such as the double-strand breaks (DSBs). An excess of micronucleated peripheral lymphocytes was found in subjects with cancer or inflammatation-based diseases. We set out to investigate the expression of genome damage, from DNA lesions to chromosome mutations (micronuclei), in overweight and obese children. Using the γ-H2AX focus assay and micronucleus (MN) test, we analyzed peripheral lymphocytes from 119 Italian children classified as normal weight (n=38), overweight (n=20), or obese (n=61). Cultures treated with bleomycin (BLM) were also set up for each child in both assays to check functioning of the apparatus that ensures DNA integrity. We measured serum TNF-α, IL-6, and C-reactive protein (CRP) as markers of inflammation. Overweight and obese children had significantly higher levels of H2AX phosphorylation (0.0191±0.0039 and 0.0274±0.0029 γ-H2AXF/n) and increased MN frequencies (2.30±0.25 and 2.45±0.22[per thousand]) than normal-weight children (0.0034±0.0006 γ-H2AXF/n, and 0.92±0.12[per thousand] MN), while all subjects responded to BLM induction, irrespective of their weight status. The fold increase of spontaneous MN frequencies in overweight and obese subjects was 2.5 and 2.7, respectively, well below the corresponding increase in the γ-H2AX foci (5.6- and 8.0-fold, respectively). IL-6 and CRP mean values were significantly higher in obese and overweight children than in controls. Here, we demonstrated that peripheral cells of overweight and obese children showed increased levels of DSBs, which were not completely repaired as part of them has been converted into micronuclei. Characterization of childhood obesity inflammation could be implemented using molecular markers of genome damage.--Scarpato, R., Verola, C., Fabiani, B., Bianchi, V., Saggese, G., Federico, G. Nuclear damage in peripheral lymphocytes of obese and overweight Italian children as evaluated by the γ-H2AX focus assay and micronucleus test.